Pengaruh Konsentrasi dan Lama Perendaman Air Kelapa pada Proses Invigorasi terhadap Viabilitas Benih Kedelai (Glycine max (L.) Merrill) - Ach. Hilmy Tafanto Putra; Budi Wijayanto; Agus Wartapa (Universitas Sebelas Maret, 2022)
This study aimed to determine the effect of concentration and duration of soaking coconut water and their interaction on the invigoration process on soybean seed viability. The study was conducted in March-May 2022 at the Greenhouse of the Agricultural Development Polytechnic of Yogyakarta Magelang and was an experimental study with a factorial, completely randomized design. Factor I in the form of concentration of coconut water with four levels of treatment, namely 0, 25, 50, and 75%, and factor II in the form of soaking time with three levels of treatment, namely 3, 6, and 9 hours. There were 12 treatment combinations with three replications each. The variables observed were germination, maximum growth potential, growth speed, vigor index, growth synchronously, plant height, and the number of leaves. Observational data were analyzed using analysis of variance (ANOVA). The results showed that the concentration of coconut water on invigoration had a significant effect on the viability of soybean seeds on the parameters of germination, maximum growth potential, growth speed, growth synchronously, and plant height and had no significant effect on the parameters of vigor index and several leaves. The duration of soaking coconut water in invigoration significantly affected soybean seed viability on the parameters of growth speed and growth simultaneously and had no significant effect on germination parameters, maximum growth potential, vigor index, plant height, and the number of leaves. There was no interaction between the concentration and duration of soaking coconut water on the viability of soybean seeds on all parameters.